Pengaruh Social Media Marketing, Electronic Word of Mouth, dan Brand Awareness terhadap Keputusan Pembelian Produk Dagadu Djokdja Melalui Minat Beli sebagai Variabel Intervening - Ansar, Muhammad; Udayana, IBN; Maharani, Bernadetta Diansepti (Jurnal Ilmiah Global Education, 2024)
This research aims to analyze the influence of Social Media Marketing, Electronic Word of Mouth (E-WoM), and Brand Awareness on Purchase Decisions for Dagadu Djokdja products through Purchase Interest as an intervening variable. This type of research is quantitative research and the sampling technique uses purposive sampling with a sample of 160 respondents. Data collection was carried out through distributing questionnaires and processing them using the SPSS application. The results of this research indicate that Purchase Interest can mediate the influence of Social Media Marketing, E-WoM, and Brand Awareness on Purchase Decisions for Dagadu Djokdja products. Meanwhile, the results of the t-test (partial test) show that Social Media Marketing, Electronic Word of Mouth (E-WoM), and Brand Awareness each have a significant influence on Purchase Interest, and the Purchase Interest variable has a significant influence on Purchase Decisions.